ORGANIZATION OF EFFECTIVE METHODS OF PREVENTION AND DETECTION OF LESIONS OF DOMESTIC BIRDS WITH HELMINTHIC DISEASES ON THE TERRITORY OF THE CITY OF ARYS, TURKESTAN REGION - Baizhanov, K. S.; Turumbetov, B. S.; Kuzerbayeva, A. T.; Doshhanov, D. A. (Жәңгір хан атындағы БҚАТУ, 2024)
This article examines the dynamics of damage and preventive measures to the most common types of helminths (Ascaridia, Heterakis, Capillaria) that parasitize domestic birds in the territory of the Arys District of the Turkestan region. The aim of this research is to acquire expertise in helminthological investigation techniques. The practical importance of this study lies in the significant role that helminthiasis plays among the diseases affecting domestic chickens, which can lead to economic challenges within the poultry industry. Some helminths of domestic chickens cause mass death on the farm, exposing all birds to disease. Many types of helminthiases are chronic and provide gradual molting of the bird, inhibit the development of young chickens. Among the diseases of poultry in the Arys District of the Turkestan region, helminthiasis occupies a large place and is known to bring an economic crisis to poultry farming, therefore, to identify effective ways of measures to prevent and combat helminthiasis. Diagnosis of helminthiasis in domestic chickens during life does not give the desired result based on clinical signs, since these symptoms resemble the symptoms of other diseases. Therefore, the diagnosis of helminthiasis in birds during life is based on laboratory research methods, when the presence or absence of helminth eggs, parts of the body, and sometimes parasitic adult worms in the feces is determined. At the heart of helminthocoprological research is the study of fecalias by macroscopic and microscopic means.
Baizhanov, K. S. Оrganization of effective methods of prevention and detection of lesions of domestic birds with helminthic diseases on the territory of the city of arys, turkestan region / K. S. Baizhanov, B. S. Turumbetov, A. T. Kuzerbayeva, D. A. Doshhanov [et al.]. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - № 4-1 (77). - Р. 233-241 (Uralsk).
Keywords: helminthology; poultry; coprological method; macroscopy; helminthoscopy; fecalia; eggs